Apophasis and pseudonymity in Dionysius the Areopagite : 'no longer I' - Stang, Charles M., 1974- (Oxford : Oxford University Press, 2012)
This text examines the writings of an early 6th century Christian mystical theologian who wrote under the name of a convert of the apostle Paul, Dionysius the Areopagite, and argues that the pseudonym and the corresponding influence of Paul are the crucial lens through which to read this influential corpus.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Keywords: Pseudo-Dionysius, -- the Areopagite; Neoplatonism; Christianity -- Philosophy -- History -- To 1500.